English for Non-English Departments: In Search for an Essential Home Base - Indah Winarni (Universitas Negeri Malang, 2016)
Promoting the quality of English for the students of non English Departments (henceforth English for undergraduates), which has been characterized as lacking prestige and resources, requires a serious promotion of its status. This means providing a proper home base for the English instructors where standards of profession and quality of service can be pursued, through a solid structure which could nurture academic culture. This paper will describe the various types of the existing structures of English for undergraduates. Illustration on the perseverance of Brawijaya University English instructors in searching for the intended home base through various efforts in staff development and serious research will be presented. What is meant by intended homebase is inspired by Swales's concept of discourse community